Primary breast lymphoma: A case series and review (Indian Journal of Case Reports, 2020)
The primary breast lymphoma (PBL) is a rare manifestation of extranodal non-Hodgkin’s lymphoma. The clinical features are indistinguishable to that of breast carcinoma. They usually do not have characteristic clinical and imaging findings. The pre-operative diagnosis of PBL is difficult and the diagnosis is based on biopsy and immunohistochemical staining. Diffuse large B-cell lymphoma is the most common histological diagnosis. We retrospectively analyzed four cases of PBL who attended at our center, between 1997 and 2019 and discussed to determine the common clinical features and therapy. These cases were originally treated by chemotherapy, that is, rituximab-cyclophosphamide, doxorubicin, vincristine, and prednisolone (R-CHOP/CHOP) or combined chemotherapy and radiotherapy and had recurrence in the central nervous system (CNS). Due to the high incidence of CNS involvement in these patients, many authors strongly believe that patients with aggressive forms of PBL should receive CNS prophylaxis, even in the early stages, as this may improve the outcome and significantly reduce the risk of a CNS relapse.